Optimalisasi Penyewaan Ruangan di PT.Technolife Menggunakan Metode Linear Programming - Tryana, Anjas; Rahmawati, Tina Rahmawati; Budiman, Tedi; Nugraha, M. Fahmi Nugraha (INTERNAL (Information System Journal), 2025)
This study aims to optimize the room rental strategy at PT.Technolife through the application of Linear Programming (LP). The company faces challenges in maximizing revenue with limited resources, including operational time and the maximum capacity of available rooms. To address these challenges, LP methods were employed using two main approaches: the graphical method and the simplex method, to determine the most profitable room rental combination. The results of the study indicate that the optimal rental combination can meet existing constraints while maximizing revenue. The study concludes that the LP method can be an effective tool in supporting strategic decision-making for room rental business management. By applying the findings of this study, PT.Technolife can optimize its revenue, improve operational efficiency, and provide better services to its customers. The implementation of this method can also be applied to similar companies to manage resources more effectively.